DESIGNING AND FORMING AN ACCOUNTING RECORDING SYSTEM USING MICROSOFT ACCESS ON CV. PRIMA JAYA MANDIRI SUKSES - Kristina Oktiviani; Natalis Christian (ConCEPt - Conference on Community Engagement Project, 2022)
Prima Jaya Mandiri Sukses is an MSMEs (Micro, Small and Medium Enterprises) that specializes in Air Conditioner, Solar Water Heater, Water Piping, Etc. CV. Prima Jaya Mandiri Sukses still uses an accounting recording which is manually recorded in the recapitulation book. So this raises the risk of accounting records being less accurate and unable to make good decisions for the company in the future. Therefore, this community services aims to design a simple accounting record system using Microsoft Access to overcome the problems of financial recording in the MSMEs. The method used in data collection are interview and observation. This recording system is designed according to the needs of the MSMEs. The designed accounting system has been implemented in CV. Prima Jaya Mandiri Sukses. The system produces reliable and accurate financial reports. Recommendations for the upcoming researchers are to be able to update the accounting system in accordance with the times that occur in the future and make it easier for other MSMEs to record and report financially.